A low-temperature silicon-based negative electrode compatible polymer electrolyte and preparation method thereof and lithium-ion battery

By using low-temperature silicon-based anode compatible polymer electrolyte in lithium-ion batteries, the problem of volume expansion of silicon-based anode materials during charging and discharging and incompatible with traditional electrolytes is solved, and high capacity retention and cycle stability are achieved. Improves the overall performance of the battery.

CN117855599BActive Publication Date: 2025-02-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410070640.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-02-07
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material during charging and discharging results in capacity decay and is incompatible with traditional electrolytes, resulting in SEI generation and battery failure.

Method used

Using a low-temperature silicon-based negative electrode compatible polymer electrolyte, the pre-cycle electrolyte is pre-heated and polymerized to form a gel solid electrolyte, including lithium salt, 1,3,5-trioxane and organic solvents, such as methyl propionate. Ester, optimize electrolyte formulation for improved compatibility and cycle stability.

Benefits of technology

The high capacity retention rate and cycle stability of the silicon-based negative electrode at low temperatures are achieved, which reduces the sensitivity of conductivity to temperature and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117855599B_ABST
    Figure CN117855599B_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature silicon-based negative electrode compatible polymer electrolyte, a preparation method thereof and a lithium ion battery. The electrolyte is obtained by pre-circulating a precursor electrolyte and then heating and polymerizing it. The precursor electrolyte comprises at least a lithium salt, 1,3,5-trioxane and an organic solvent, and the organic solvent comprises at least methyl propionate. Aiming at the problem that the liquid component of the existing TXE-based electrolyte crystallizes at low temperatures, resulting in relatively low ion conductivity, a low-freezing point solvent modification strategy is proposed. By using an organic solvent containing methyl propionate with a low freezing point, the sensitivity of the ion conductivity of the polymer electrolyte to temperature is reduced, rapid ion conduction at low temperatures is achieved, and the silicon-based negative electrode has a high capacity retention rate at low temperatures. At the same time, a pre-circulation treatment is performed through a formation reaction to improve the silicon-based negative electrode interface and further improve the cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a low-temperature silicon-based negative electrode compatible polymer electrolyte and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long life, and environmental friendliness, and are widely used in mobile electronic devices and electric vehicles. However, with the innovation of technology, consumers currently have higher requirements for the energy density of lithium-ion batteries.

[0003] Graphite is currently the most widely used negative electrode material, with a theoretical specific capacity of 372 mAh g -1 , which can no longer meet the market demand for high energy density. Therefore, the search for the next generation of lithium-ion battery negative electrode materials has become a hot topic in current research. Silicon-based negative electrode materials are considered to be ideal negative electrode materials for the next generation of lithium-ion batteries due to their high theoretical specific capacity and suitable lithium insertion potential.

[0004] However, silicon-based negative electrodes have obvious disadvantages. For example, during the charge and discharge process, the silicon-based negative electrode will undergo a large volume expansion, causing the material to pulverize or even fall off, thereby leading to a sharp decline in capacity. In addition, silicon-based negative electrode materials are incompatible with traditional electrolytes, resulting in the electrolyte continuously reacting on the surface of the silicon-based negative electrode to generate SEI during the charge and discharge process, which will also cause the electrode capacity to decay and the electrolyte to be depleted, and ultimately the battery fails.

[0005] In order to solve the problems of silicon-based negative electrode materials. The commonly used electrolyte strategy is to introduce fluoroethylene carbonate (FEC) into the electrolyte to form a uniform and stable SEI layer to improve the electrochemical performance of silicon-based negative electrodes. However, insufficient addition of FEC will also lead to the attenuation of battery performance in the later stage. In addition, traditional lithium batteries use volatile, flammable, and leaky organic liquid electrolytes, which pose a great safety hazard. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a low-temperature silicon-based negative electrode compatible polymer electrolyte.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0010] (i) obtained by pre-circulating the precursor electrolyte and then heating and polymerizing;

[0011] (ii) the precursor electrolyte comprises at least a lithium salt, 1,3,5-trioxane and an organic solvent;

[0012] (iii) the organic solvent comprises at least methyl propionate;

[0013] (iv) The mass ratio of the organic solvent to 1,3,5-trioxane is 7:3 to 3:7.

[0014] As a preferred solution of the low-temperature silicon-based negative electrode compatible polymer electrolyte described in the present invention, the precursor electrolyte also includes additives, including one or more of lithium difluorophosphate (LiPF2O2), lithium nitrate (LiNO3), difluoroethylene carbonate (DFEC), vinyl sulfate (DTD), 2-cyanoethyltriethoxysilane (TEOSCN), methyl trifluoroethyl carbonate (FEMC), di(2,2,2-trifluoroethyl) carbonate (DTFEC), and vinylene carbonate (VC), and the added amount is 0 to 10% of the precursor electrolyte.

[0015] As a preferred embodiment of the low-temperature silicon-based negative electrode compatible polymer electrolyte described in the present invention, the organic solvent further includes at least one or more of fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), methyl trifluoroethyl carbonate (FEMC), trifluoropropylene carbonate (TFPC), di(2,2,2-trifluoroethyl) carbonate (DTFEC), ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl acetate (EA), methyl acetate (MA), methyl sulfite (DMS), diethyl sulfite (DES), and ethyl methyl sulfite (EMS), and the mass ratio with methyl propionate (MP) is 1:9 to 7:3.

[0016] As a preferred solution of the low-temperature silicon-based negative electrode compatible polymer electrolyte described in the present invention, the lithium salt includes one or more of lithium difluorooxalatoborate (LiDFOB), lithium hexafluorophosphate (LiPF6), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFBOP), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), and lithium bis(fluorosulfonyl imide) (LiFSI), and the concentration in the precursor electrolyte is 0.4-5 mol / L.

[0017] Another object of the present invention is to provide a method for preparing a low-temperature silicon-based negative electrode compatible polymer electrolyte.

[0018] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0019] The precursor electrolyte is injected into the lithium-ion battery, pre-circulated through a formation reaction, and then heated and polymerized to convert the liquid electrolyte into a gel solid state, thereby obtaining a low-temperature silicon-based negative electrode compatible polymer electrolyte;

[0020] Wherein, the precursor electrolyte at least includes lithium salt, 1,3,5-trioxane and an organic solvent.

[0021] As a preferred solution of the method for preparing the low-temperature silicon-based negative electrode compatible polymer electrolyte of the present invention, wherein: the formation reaction is a pre-cycle treatment using a current of 0.01C to 0.2C for 1 to 10 times.

[0022] As a preferred solution of the method for preparing the low-temperature silicon-based negative electrode compatible polymer electrolyte of the present invention, the heating temperature of the heating polymerization is 60 to 90° C., and the heating time is 2 to 36 hours.

[0023] Another object of the present invention is to provide an application of a low-temperature silicon-based negative electrode compatible polymer electrolyte in the preparation of a low-temperature silicon-based negative electrode lithium-ion battery.

[0024] Another object of the present invention is to provide a low-temperature silicon-based negative electrode lithium-ion battery, including a low-temperature silicon-based negative electrode compatible polymer electrolyte.

[0025] As a preferred solution of the low-temperature silicon-based negative electrode lithium-ion battery described in the present invention, the low-temperature silicon-based negative electrode lithium-ion battery also includes a silicon negative electrode as a working electrode, a lithium sheet as a counter electrode and a reference electrode, and Celgard as a diaphragm.

[0026] Beneficial effects of the present invention:

[0027] The present invention aims to solve the problem that the liquid components of existing TXE-based electrolytes crystallize at low temperatures, resulting in relatively low ionic conductivity. A low-freezing-point solvent modification strategy is proposed. By using an organic solvent containing methyl propionate with a low freezing point, the sensitivity of the ionic conductivity of the polymer electrolyte to temperature is reduced, rapid ion conduction at low temperatures is achieved, and the silicon-based negative electrode has a high capacity retention rate at low temperatures. At the same time, a pre-cycling treatment is performed through a formation reaction to improve the silicon-based negative electrode interface and further improve the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0029] Figure 1 The conductivity of the electrolyte of Example 1 of the present invention at different temperatures.

[0030] Figure 2 The cycling performance of the electrolytes of Example 1 of the present invention and Comparative Examples 1 to 3 are compared. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0035] The electrolyte / electrolyte performance test method in the present invention refers to:

[0036] A half-cell was made with a silicon negative electrode as the working electrode, a lithium sheet as the counter electrode and the reference electrode, and Celgard (polypropylene, pp) as the separator. The amount of electrolyte in each half-cell was 50 μL.

[0037] At room temperature (25°C), the voltage was set at 0.1A g between 0.01V and 1V. -1 Charge and discharge 3 times, then -1 Carry out long cycle charge and discharge;

[0038] Calculate the capacity retention rate of the battery after 100 cycles, where the Nth capacity retention rate of the battery cycle (%) = Nth week charging capacity / fourth charging capacity × 100%

[0039] The ionic conductivity test method in the present invention is:

[0040] The lithium ion conductivity was tested using a blocking cell, with stainless steel used for both the positive and negative electrodes. The internal resistance R (Ω) of the polymer electrolyte was obtained by EIS testing, with an amplitude of 10 mV and a test frequency of 1×10 5 ~0.01Hz. The lithium ion conductivity can be calculated according to the following formula:

[0041]

[0042] Where σ (S / cm) is the ionic conductivity, L (cm) is the thickness of the polymer electrolyte, and S (cm 2 ) is the effective area of ​​contact between the polymer electrolyte and the positive and negative electrodes.

[0043] Example 1

[0044] This embodiment provides a method for preparing a low-temperature silicon-based negative electrode compatible polymer electrolyte, specifically:

[0045] 1) Prepare the precursor electrolyte;

[0046] Lithium salts: lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);

[0047] Organic monomer: 1,3,5-trioxane (TXE);

[0048] Organic solvents: methyl propionate (MP), fluoroethylene carbonate (FEC);

[0049] Additives: diethyl sulfate (DTD);

[0050] The concentration of LiDFOB is 0.4 mol / L, the concentration of LiTFSI is 0.6 mol / L, the mass ratio of TXE:FEC:MP is 4:2:4, and the content of DTD is 3 wt%.

[0051] 2) preparing electrolyte;

[0052] The prepared precursor electrolyte was injected into the lithium-ion battery, and after three pre-cycles, it was heated and reacted at 70°C for 6 hours to convert the electrolyte into a gel solid electrolyte, thereby obtaining a silicon-based negative electrode compatible polymer electrolyte.

[0053] Figure 1 The conductivity of the electrolyte prepared in this example at different temperatures shows that the ionic conductivity of the polymer electrolyte is less sensitive to temperature and can achieve rapid ion conduction at low temperatures.

[0054] Example 2

[0055] This example is used to explore the effect of different types of composite organic solvents on the performance of the electrolyte. Specifically, the other organic solvent in Example 1 except MP is adjusted to FEC, DFEC, TFPC, FEM, PC, and the remaining steps and processes are all referred to Example 1 to obtain electrolytes made of different organic solvents, and the relevant properties are measured, as shown in Table 1.

[0056] Table 1 Comparison of electrolyte properties prepared by different organic solvents

[0057]

[0058] As can be seen from Table 1, the type of composite organic solvent of the present invention has a significant effect on the performance of the electrolyte. Methyl propionate has a low freezing point, which reduces the sensitivity of the ionic conductivity of the polymer electrolyte to temperature. When it is used in combination with other solvents, it can further optimize the performance of the electrolyte, promote the movement of ions in the electrolyte, and improve the ionic conductivity.

[0059] Example 3

[0060] This example is used to explore the effect of different ratios of composite organic solvents on the performance of the electrolyte. Specifically, the ratio of MP to FEC in the example is adjusted to 4:2, 3:3, 2:4, and 1:0. The remaining steps and processes are all based on Example 1 to obtain electrolytes prepared with different organic solvent ratios, and the relevant properties are measured, as shown in Table 2.

[0061] Table 2 Comparison of electrolyte performances obtained with different composite organic solvent ratios

[0062]

[0063]

[0064] As can be seen from Table 2, the proportion of the composite organic solvent has a significant effect on the performance of the electrolyte. This embodiment further optimizes the proportion based on the optimization of Example 2. Appropriate adjustment of the ratio of fluoroethylene carbonate to methyl propionate can achieve optimal low-temperature cycle stability and ionic conductivity. Too high or too low fluoroethylene carbonate content may lead to a decrease in the performance of the electrolyte. Too high a fluoroethylene carbonate content may increase the viscosity of the electrolyte and affect the ion transfer rate; too low a fluoroethylene carbonate content may cause the solid electrolyte interface film generated on the electrode surface to be unstable, thereby causing a decrease in battery performance.

[0065] Example 4

[0066] This example is used to explore the effect of additives on electrolyte performance, specifically adjusting the type and amount of additives. The remaining steps and processes are all referred to Example 1 to prepare electrolytes under different additive conditions in this example. For specific variables and performance tests, refer to Table 3.

[0067]

[0068] Different types of additives and their dosage also have a significant effect on electrolyte performance, because additives can change the ion exchange in the electrolyte and the electrode interface properties. For example, some additives can enhance the exchange capacity of cations or anions in the electrolyte, thereby improving the ion conductivity of the electrolyte. Some additives can decompose on the electrode surface to form a good solid electrolyte film to improve battery performance. Therefore, the type and amount of additives may affect the ion transport rate of the electrolyte and the characteristics of the electrode / electrolyte interface. By adjusting the type and amount of additives in the electrolyte, the electrochemical performance of the battery can be optimized.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 1 is that the precursor electrolyte is directly injected into the lithium-ion battery as the electrolyte without post-treatment.

[0071] Comparative Example 2

[0072] The difference between this comparative example and Example 1 is that the precursor electrolyte is directly injected into the lithium-ion battery without pre-circulation treatment, and the electrolyte is only heated at 70° C. for 6 hours to convert the electrolyte into a gel solid electrolyte.

[0073] Comparative Example 3

[0074] The difference between this comparative example and Example 1 is that the precursor electrolyte formula is adjusted to

[0075] 1 mol / L LiPF6, the solvent is EC and EMC (mass ratio 3:7), the additive is FEC, and the additive content accounts for 5% of the electrolyte mass.

[0076] The remaining steps and processes are all referred to Example 1 to obtain the electrolyte of this comparative example.

[0077] The cycle performance of the half-cells assembled with the electrolytes of Comparative Examples 1 to 3 was tested and compared with that of Example 1. The results are shown in Table 4 and Figure 2 shown.

[0078] Table 4 Performance comparison of half-cells under different treatment schemes

[0079]

[0080] In summary, the present invention aims at the problem that the liquid components of the existing TXE-based electrolytes crystallize at low temperatures, resulting in relatively low ionic conductivity. A low-freezing-point solvent modification strategy is proposed. By using an organic solvent containing methyl propionate with a low freezing point, the sensitivity of the ionic conductivity of the polymer electrolyte to temperature is reduced, rapid ion conduction at low temperatures is achieved, and the silicon-based negative electrode has a high capacity retention rate at low temperatures. At the same time, pre-cycling treatment is carried out through a formation reaction to improve the silicon-based negative electrode interface and further improve the cycle stability.

[0081] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A low-temperature silicon-based negative electrode compatible polymer electrolyte, characterized in that: include, It is obtained by pre-circulating the precursor electrolyte and then heating and polymerizing; The precursor electrolyte is composed of lithium salt, 1,3,5-trioxane, organic solvent and additives; The lithium salt is composed of lithium difluorooxalate borate and lithium bis(trifluoromethanesulfonyl)imide, the organic solvent is composed of methyl propionate and fluoroethylene carbonate, and the additive is vinyl sulfate; The concentration of lithium difluorooxalatoborate was 0.4 mol / L, the concentration of lithium bistrifluoromethanesulfonyl imide was 0.6 mol / L, the mass ratio of 1,3,5-trioxane:methyl propionate:fluoroethylene carbonate was 4:2:4, and the content of vinyl sulfate was 3 wt%.

2. The method for preparing a low-temperature silicon-based negative electrode compatible polymer electrolyte according to claim 1, characterized in that: include, The precursor electrolyte is injected into the lithium-ion battery, pre-circulated through a formation reaction, and then heated and polymerized to convert the liquid electrolyte into a gel solid state, thereby obtaining a low-temperature silicon-based negative electrode compatible polymer electrolyte.

3. The method for preparing a low-temperature silicon-based negative electrode compatible polymer electrolyte according to claim 2, characterized in that: The formation reaction is performed by using 0.01 C to 0.2 C current for 1 to 10 pre-cycle treatments.

4. The method for preparing a low-temperature silicon-based negative electrode compatible polymer electrolyte according to claim 2, characterized in that: The heating temperature of the heating polymerization is 60-90° C., and the heating time is 2-36 hours.

5. Use of the low-temperature silicon-based negative electrode compatible polymer electrolyte as claimed in claim 1 in the preparation of a low-temperature silicon-based negative electrode lithium-ion battery.

6. A low-temperature silicon-based negative electrode lithium-ion battery, characterized in that: It comprises the low-temperature silicon-based negative electrode compatible polymer electrolyte as described in claim 1.

7. The low-temperature silicon-based negative electrode lithium-ion battery according to claim 6, characterized in that: The low-temperature silicon-based negative electrode lithium-ion battery also includes a silicon negative electrode as a working electrode, a lithium sheet as a counter electrode and a reference electrode, and Celgard as a diaphragm.

Citation Information

Patent Citations

  • Solid-state alkali metal-like secondary battery and preparation of gel electrolyte thereof

    CN117374381A